Esternalità e sviluppo industriale di lungo periodo in Italia. Un'analisi a livello provinciale - Giulio Ciannelli; Riccardo Leoncini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
– The aim of this paper is to provide, following an approach recently developed by Glaeser et al. (1992), an empirical investigation on the role of dynamic externalities in industrial agglomeration and long-run industrial development. By means of a very large dataset containing information at provincia level for 16 sectors of Italian manufacturing industry covering a thirty year period (1961-1991), geographical specialisation and variety of the local production are investigated, for both Italy and four geographical areas (North-West, North-East, South-East and South-West). It is argued that history matters, that is, initial conditions explain a very large share of industrial agglomeration, but within the geographical areas very different patterns of externalities emerge, as well as different local labour markets for the North and South of Italy.
Keywords: 330